KEDUDUKAN KEPEMILIKAN HAK ATAS TANAH DALAM PERKAWINAN CAMPURAN TANPA ADANYA PERJANJIAN PISAH HARTA - Pratama, Adhitya Dimas (Jurnal Panorama Hukum, 2018)
Intermarriage is a phenomenon that is rife with the development of increasingly rapid technology weapons. Implementation of mixed marriages must not be separated from the constraints and risks will dihadi offender Mixed Marriage itself. One of the problems that arise are related to the occurrence of the Joint Treasure especially over land rights as legal consequences arising from the holding of intermarriage intermarriage especially if implemented without prenuptial agreement. The author of this thesis wants to study and analyze more about the law as a result of intermarriage without severance agreement treasure to land ownership and settlement of land ownership issues arising from mixed marriage without separation agreement treasure. The method used is a normative legal research, namely legal research done by researching library materials or secondary law while in locating and collecting data is done by two approaches, namely legislation and conceptual approaches. The results showed that the legal consequences of intermarriage in the absence of agreement separating property to the ownership rights to the land after the enactment of Law No. 1 of 1974 About the marriage, property acquired during the marriage is community property as engaging joint property so that if it is not made an prenuptial agreement the property rights to land shall be released within a period of one (1) year or the land falls to the state. The resolution attempts to do to the problems of land ownership arising from mixed marriages without the agreement split the treasure is in the form of drafting of a treaty mate after marriage or reduction of land rights from property rights into rights of use in accordance with the provisions of that kind of tenure, which may possess by someone follow the status of their land rights subjects in accordance with the provisions of the legislation